2014
DOI: 10.1186/1476-4598-13-138
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-mangostin inhibits intracellular fatty acid synthase and induces apoptosis in breast cancer cells

Abstract: BackgroundFatty acid synthase (FAS) has been proven over-expressed in human breast cancer cells and consequently, has been recognized as a target for breast cancer treatment. Alpha-mangostin, a natural xanthone found in mangosteen pericarp, has a variety of biological activities, including anti-cancer effect. In our previous study, alpha-mangostin had been found both fast-binding and slow-binding inhibitions to FAS in vitro. This study was designed to investigate the activity of alpha-mangostin on intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 52 publications
2
71
0
3
Order By: Relevance
“…29 It has previously been shown that -mangostin suppresses the expression and intracellular activity of fatty acid synthase, a metabolic enzyme commonly over-expressed in various cancer cell lines and crucial for their survival. 30 Additionally, -mangostin can inhibit mammalian DNA polymerase and topoisomerases, which may also contribute to its stronger toxicity towards rapidly dividing cancer cells. 31 Our data support a potential chemopreventive and chemotherapeutic potential of -mangostin for cancer treatment, but this requires further tissue specific and in vivo confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has previously been shown that -mangostin suppresses the expression and intracellular activity of fatty acid synthase, a metabolic enzyme commonly over-expressed in various cancer cell lines and crucial for their survival. 30 Additionally, -mangostin can inhibit mammalian DNA polymerase and topoisomerases, which may also contribute to its stronger toxicity towards rapidly dividing cancer cells. 31 Our data support a potential chemopreventive and chemotherapeutic potential of -mangostin for cancer treatment, but this requires further tissue specific and in vivo confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the close association between FASN, obesity and breast cancer, the studies of FASN inhibitors have indicated their role as targets for chemotherapy in breast cancer and a novel strategy for antineoplastic intervention (18). In fact, previous studies demonstrated that certain synthetic and natural FASN inhibitors, including C75, desoxyrhaponticin, rhaponticin and α-mangostin may lead to selective cytotoxicity in FASN over-expressing cancer cell lines (18)(19)(20). This result suggested again that the pharmacological inhibition of FASN may represent a potential target for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…SK-BR-3 cells were seeded in 96-well plate firstly, at a density about 5x10 3 cells/well and then treated with purified patuletin in different concentrations (5,10,20,40, 80 or 160 µM) for 24 h. Thereafter, 5 mg/ml MTT solution was added into each well and incubated for 4 h at 37˚C. Then, the medium with MTT was aspirated, 200 µl DMSO/well was added to the wells and the cells were incubated for 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that inhibition of FAS may induce cell apoptosis via reducing fatty acids (12,14,32) These results support the significant role of FAS in SK-BR-3 cells and propose that FAS is the aim that curcumin act on.…”
Section: Discussionmentioning
confidence: 70%
“…50 µL Particlefree supernatant, 25 mM potassium Phosphate buffer, 0.25 mM EDTA, 0.25 mM dithiothreitol (DTT), 30 µM acetyl-CoA, and 350 µM NADPH (pH 7.0) in a total volume of 500 µL were Observed at 340 nm for 100 s to measure NADPH oxidation. After the addition of 100 µM of malonyl-CoA, the reaction was tested for an additional 1 minutes to designate FAS-dependent oxidation of NADPH (14). The change in concentration of NADPH during oxidation was measured using the following formula: ∆C = ∆A/E…”
Section: Fas Activity Assaymentioning
confidence: 99%